Jawabanmu

2014-05-28T00:14:06+07:00
F(x) =   x^{2} -4x-5 /  x^{2} -1
f '(x) = 2x-4 / 2x = 2 (x-2) / 2x
       = x-2 / x

F '(0) = 0 - 2 / 0 = 0
f '(3) = 3 - 2 / 3 = 1/3
f (2) = 2 ^{2} - 4 (2) - 5 / 2 ^{2} -1
       = 4 - 8 - 5 / 3
       = -9/3 = -3

jadi, F '(0) + f '(3) - f (2) = 0 + 1/3 - (-3) = 1/3 + 3 = 10/3
f'(0) = 4(0)^2 + 8(0) + 4 / ((0)^2 - 1)^2
= 4
f'(3) = 4(3)^2 + 8(3) + 4 / ((3)^2 - 1)^2
= 64/64 = 1
f (2) = 2^2 - 4(2) - 5 / 2^2 - 1

f'(0) + f'(3) - f (2) = 4 + 1 - (-3) = 8
f'(0) = 4(0)^2 + 8(0) + 4 / ((0)^2 - 1)^2
= 4
f'(3) = 4(3)^2 + 8(3) + 4 / ((3)^2 - 1)^2
= 64/64 = 1
f (2) = 2^2 - 4(2) - 5 / 2^2 - 1

f'(0) + f'(3) - f (2) = 4 + 1 - (-3) = 8
f'(0) = 4(0)^2 + 8(0) + 4 / ((0)^2 - 1)^2
= 4
f'(3) = 4(3)^2 + 8(3) + 4 / ((3)^2 - 1)^2
= 64/64 = 1
f (2) = 2^2 - 4(2) - 5 / 2^2 - 1

f'(0) + f'(3) - f (2) = 4 + 1 - (-3) = 8
f'(0) = 4(0)^2 + 8(0) + 4 / ((0)^2 - 1)^2
= 4
f'(3) = 4(3)^2 + 8(3) + 4 / ((3)^2 - 1)^2
= 64/64 = 1
f (2) = 2^2 - 4(2) - 5 / 2^2 - 1

f'(0) + f'(3) - f (2) = 4 + 1 - (-3) = 8
maaf y trlalu banyak..
erorr pnya ku barusan